Peningkatan Capacity Building Aparatur Nagari: Pendampingan Pembentukan Badan Usaha Milik Nagari - Boni Saputra; Hidayatul Fajri; Pratiwi Nurhabibie; Dwi Finna Syolendra (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This community service partner is the Preparation Nagari Government Lingkuang Aua Bandarejo and Preparation Nagari Government Mahakarya, which are two of the seventy-two Nagari resulting from the division in West Pasaman Regency in 2018 based on the Minister of Home Affairs Regulation Number 01 of 2017 concerning Village Arrangements. It is known that the Nagari resulting from this division does not yet have a Nagari-Owned Enterprise (BUM-Nag). So the purpose of this service activity is to provide assistance and counseling about the formation of BUM-Nag, contribute ideas and describe the importance of the existence of BUM-Nag. BUM-Nag is an alternative business entity that needs to be developed to encourage the Nagari economy, with the hope of creating new economic resources for Nagari to use and for the welfare of the Nagari community. Methods and approaches used: education, socialization, training, and mentoring “participatory rural appraisal”. This training phase begins with a survey and the establishment of goals and objectives to be achieved. This service program has a significant impact in increasing the knowledge, abilities, and skills of partners in the preparation of Nagari regulations regarding the formation of BUM-Nag, and partners can understand well about strengthening BUM-Nag institutions.